PKM PANTI ASUHAN DI KOTA PEKANBARU UNTUK PENINGKATAN KETERAMPILAN BELAJAR DAN SOFTSKILL - Yeeri Badrun; Sri Fitria Retnawaty; Yulia Fitri (LPPM UMRI, 2018)
Specifically the problem for orphanage children is that there is still a weak ability to master the learning material quickly (Quantum Learning) and soft skills. The observations at the Orphanage showed that the development of material for mastering rapid learning skills (Quantum Learning) and soft learning was still very little. In addition, the lack of learning media facilities also inhibits the improvement of rapid learning skills (Quantum Learning) and soft skills for the orphanage children. To answer these problems, UMRI collaborated with Putri Aisyiah Orphanage and Al Hasanah Orphanage in community partnership activities in line with the Ristekdikti Program. Both of these Orphanages are in the same area as Muhammadiyah Riau University in Pekanbaru City. Putri Aisyiah Orphanage Pekanbaru was established in 1979 and currently carries 31 people. While the Al-Hasanah Orphanage was established in 2000 and currently carries 90 children. In this program, Quantum Learning and soft skill material have been given the target of increasing the ability to learn quickly and instill character strengthening, ethics. Then the ToT Quantum Learning and Softskill workshop was carried out to the orphanage building teacher. This activity was published in the media and the publication of scientific journals.